Selectively Inhibiting the Median Preoptic Nucleus Attenuates Angiotensin II and Hyperosmotic-Induced Drinking Behavior and Vasopressin Release in Adult Male Rats - Marciante, Alexandria B. (eNeuro, 2019)
The median preoptic nucleus (MnPO) is a putative integrative region that contributes to body fluid balance. Activation of the MnPO can influence thirst, but it is not clear how these responses are linked to body fluid homeostasis. We used designer receptors exclusively activated by designer drugs (DREADDs) to determine the role of the MnPO in drinking behavior and vasopressin release in response to peripheral angiotensin II (ANG II) or 3% hypertonic saline (3% HTN) in adult male Sprague Dawley rats (250–300 g). Rats were anesthetized with isoflurane and stereotaxically injected with an inhibitory DREADD (rAAV5-CaMKIIa-hM4D(G(i))-mCherry) or control (rAAV5-CaMKIIa-mCherry) virus in the MnPO. After two weeks’ recovery, a subset of rats was used for extracellular recordings to verify functional effects of ANG II or hyperosmotic challenges in MnPO slice preparations. Remaining rats were used in drinking behavior studies. Each rat was administered either 10 mg/kg of exogenous clozapine-N-oxide (CNO) to inhibit DREADD-expressing cells or vehicle intraperitoneal followed by a test treatment with either 2-mg/kg ANG II or 3% HTN (1 ml/100-g bw, s.c.), twice per week for two separate treatment weeks. CNO-induced inhibition during either test treatment significantly attenuated drinking responses compared to vehicle treatments and controls. Brain tissue processed for cFos immunohistochemistry showed decreased expression with CNO-induced inhibition during either test treatment in the MnPO and downstream nuclei compared to controls. CNO-mediated inhibition significantly attenuated treatment-induced increases in plasma vasopressin compared to controls. The results indicate inhibition of CaMKIIa-expressing MnPO neurons significantly reduces drinking and vasopressin release in response to ANG II or hyperosmotic challenge.